2020
DOI: 10.1556/004.2020.00050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of a human D-dimer test in dogs with neoplasia

Abstract: The goal of this study was to evaluate the suitability of a commercially available D-dimer assay as a diagnostic tool for testing dogs. This assay is an immunoturbidimetric diagnostic test, capable of determining the D-dimer levels in human plasma by using 2B9 monoclonal antibody. Plasma samples of clinically healthy (n = 20) and tumour-bearing (n = 50) dogs were measured. The tumours were grouped on the basis of histological type and aggressiveness, and then the measured D-dimer concentrations of these groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
2
3
0
1
Order By: Relevance
“…Previous studies have defined an approximate range of 0.1–0.5 µg/mL as reference intervals of D-dimer in normal dogs [ 23 , 38 ], which is highly similar to our findings. The current study revealed that the D-dimer concentration of 30 healthy dogs was 0.1 µg/mL.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Previous studies have defined an approximate range of 0.1–0.5 µg/mL as reference intervals of D-dimer in normal dogs [ 23 , 38 ], which is highly similar to our findings. The current study revealed that the D-dimer concentration of 30 healthy dogs was 0.1 µg/mL.…”
Section: Discussionsupporting
confidence: 91%
“…We further allocated all the dogs with tumors into three groups to evaluate whether the origin of the tumors would have an impact on the D-dimer levels. As shown in Figure 2 b, there was no significant difference among the three groups, which is relatively in line with a previous study reporting that D-dimer levels were highly similar among connective-, epithelial-, lymphatic-, and exocrine-type tumors [ 23 ]. Thus, we speculated that the origins of the tumors might play a minor role in D-dimer formation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Reportes en humanos han informado que, existe una correlación entre la agresividad del tumor y el aumento de DD y sugieren su posible uso como marcador de pronóstico [17]. Por lo tanto, su elevación se asocia de forma única con enfermedades graves que incluyen principalmente tromboembolismo, sepsis y/o cáncer [15].…”
Section: Introduccionunclassified